The impact of global terrorism on economic and political development : Afro-Asian perspectives - Das, Ramesh Chandra, 1973- (Emerald Publishing Limited, 2019)
Global economic and political systems have been facing serious threats from different terrorist groups for the last few decades, and the implications of these incidences are increasing rapidly. This edited collection seeks to address and analyse the ramifications of terrorism and terrorist activities on economic and political systems in terms of the decline in GDP levels, increase in unnecessary military expenditure at the cost of social and economic developments, disincentives to the foreign investors, loss of diplomatic powers at global levels, social unrest, and increase in youth unemployment, poverty, political violence, and more. Whilst the book considers the effects of terrorism at a world-level, there is a specific focus on the economies in the Afro-Asian regions. This unique coverage of studies in quantitative economics and political systems offers postgraduate students, researchers and academics in the fields of political economics, international relations, and defence studies, among others, the opportunity to expand their knowledge on the impact of terrorism.
Prelims -- Foreword -- Global terrorism and economic and political systems: an overall assessment -- Impact of terrorism on the economic and political systems of the Afro-Asian countries -- Index.
Includes index.
Print version record
Keywords: Terrorism -- Economic aspects; Terrorism -- Political aspects; Business & Economics -- Economics -- General; Economics